2013
DOI: 10.1136/bcr-2012-008104
|View full text |Cite
|
Sign up to set email alerts
|

Non-compaction of the left ventricular myocardium with Cor-triatriatum and associated anomalies

Abstract: Non-compaction of ventricular myocardium (NVM) is a rare clinical entity. It has been reported more frequently in recent years because of continuous improvements in imaging techniques and resolution. Although apical region of the left ventricle is the most commonly involved site, biventricular involvement has also been reported in the published literature. This abnormality is often associated with other congenital cardiac and extracardiac anomalies. We describe such a case, incidentally detected and documented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Many authors reported cases of patients presenting concomitant CHD and LVNC, including Ebstein [ 16 , 18 , 20 , 22 ], congenital atresia of the left main coronary artery [ 19 ], VSD [ 24 ], double-chambered left ventricle [ 23 ], patent ductus arteriosus [ 21 ], and also a complex congenital defect formed by cor-triatriatum , VSD, persistent left superior caval vein and an anomalous extracardiac vessel [ 17 ]. To date, however, only four studies sought to establish epidemiological associations between the two entities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors reported cases of patients presenting concomitant CHD and LVNC, including Ebstein [ 16 , 18 , 20 , 22 ], congenital atresia of the left main coronary artery [ 19 ], VSD [ 24 ], double-chambered left ventricle [ 23 ], patent ductus arteriosus [ 21 ], and also a complex congenital defect formed by cor-triatriatum , VSD, persistent left superior caval vein and an anomalous extracardiac vessel [ 17 ]. To date, however, only four studies sought to establish epidemiological associations between the two entities.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding this association could guide both clinical practice, as well as anatomy, embryology and genetic studies aiming to understand the development of LVNC. Although many authors reported cases of patients presenting concomitant CHD and LVNC [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ], to date, only four studies sought to establish epidemiological associations between the two entities. All of them, however, selected first patients known to have LVNC and looked for the prevalence of CHD among them.…”
Section: Introductionmentioning
confidence: 99%